2022
DOI: 10.21865/ridep65.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Psicométrico del Instrumento de Compromiso Escolar (SEI) en Estudiantes Secundarios en Chile

Abstract: El Student Engagement Instrument es uno de los cuestionarios más utilizados internacionalmente en la evaluación de los factores asociados al compromiso escolar. Este estudio analizó las propiedades psicométricas del "Student Engagement Instrument" (SEI) (Appleton et al., 2006) en una muestra de 452 estudiantes secundarios, entre 13 y 20 años (M=15.66; DE=1.31) pertenecientes a colegios de Concepción, Chile. Se hizo un análisis descriptivo de los datos, consistencia interna, confiabilidad temporal y un análisis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…In its original development and validation, Appleton et al (2006) reported an internal consistency with an overall Cronbach's alpha of α = .88. This instrument has recently been validated in a sample of Chilean students from the province of Concepción with and without SEN (González et al, 2022). In that sample, an acceptable internal consistency was reported, with alphas and omegas between ω = .76 y ω = .88 in each of the subscales, and it showed a good fit for the 6-factor structure validated in the study by Appleton et al (2006).…”
Section: Variables and Instrumentsmentioning
confidence: 92%
“…In its original development and validation, Appleton et al (2006) reported an internal consistency with an overall Cronbach's alpha of α = .88. This instrument has recently been validated in a sample of Chilean students from the province of Concepción with and without SEN (González et al, 2022). In that sample, an acceptable internal consistency was reported, with alphas and omegas between ω = .76 y ω = .88 in each of the subscales, and it showed a good fit for the 6-factor structure validated in the study by Appleton et al (2006).…”
Section: Variables and Instrumentsmentioning
confidence: 92%
“…Cabe señalar que ninguno de los instrumentos mencionados ha sido adaptado para la población colombiana, es importante disponer de instrumentos validados que contribuyan a la evaluación de aspectos en torno a la salud mental de la población (Garcia et al, 2021) y la importancia de realizar investigación transcultural (González et al, 2022). La AE sigue siendo un tema de interés en el ámbito científico y de investigación, debido a su impacto en el bienestar de las personas.…”
Section: Introductionunclassified